Excitable speech: A politics of the performance - Butler, Judith (Routledge, 1997)
‘When we claim to have been injured by language, what kind of claim do we make?’ - Judith Butler, Excitable Speech Excitable Speech is widely hailed as a tour de force and one of Judith Butler’s most important books. Examining in turn debates about hate speech, pornography and gayness within the US military, Butler argues that words can wound and linguistic violence is its own kind of violence. Yet she also argues that speech is ‘excitable’ and fluid, because its effects often are beyond the control of the speaker, shaped by fantasy, context and power structures. In a novel and courageous move, she urges caution concerning the use of legislation to restrict and censor speech, especially in cases where injurious language is taken up by aesthetic practices to diminish and oppose the injury, such as in rap and popular music. Although speech can insult and demean, it is also a form of recognition and may be used to talk back; injurious speech can reinforce power structures, but it can also repeat power in ways that separate language from its injurious power. Skillfully showing how language’s oppositional power resides in its insubordinate and dynamic nature and its capacity to appropriate and defuse words that usually wound, Butler also seeks to account for why some clearly hateful speech is taken to be iconic of free speech, while other forms are more easily submitted to censorship. In light of current debates between advocates of freedom of speech and ‘no platform’ and cancel culture, the message of Excitable Speech remains more relevant now than ever.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; discipline; fem1000; performativité; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; états-unis

Fields of play: Constructing an academic life - Richardson, Laurel W. (Rutgers University Press, 1997)
Comment les circonstances spécifiques dans lesquelles nous écrivons affectent-elles ce que nous écrivons ? Comment ce que nous écrivons affecte-t-il ce que nous devenons ? Comment pouvons-nous maintenir l'intégrité professionnelle et personnelle dans l'université d'aujourd'hui ? Dans une série d'écrits traditionnels et expérimentaux, aboutissement de dix années de travaux en cours, Laurel Richardson enregistre un parcours intellectuel, déplaçant les frontières et créant de nouvelles façons de lire et d'écrire. Appliquant l'imaginaire sociologique au processus d'écriture, elle relie sa vie à son travail. Profondément engageant, écrit de manière émouvante avec grâce, élégance et clarté, le livre stimule les lecteurs à situer leur propre écriture dans des contextes personnels, sociaux et politiques.
Keywords: 1900-1999; 1990-1999; amériques; arts; discipline; fem1000; littérature; premier cycle; périodes historiques; régions géographiques; thématiques; théories féministes; écriture des femmes*; états-unis; études littéraires

Contre-voix : essais de critique au féminin - Saint-Martin, Lori (Collection Essais critiques, 1997)
Keywords: 1900-1999; 1990-1999; amériques; arts; discipline; fem1000; littérature; premier cycle; périodes historiques; québec; régions géographiques; thématiques; théories féministes; écriture des femmes*; études littéraires